The role of Good Corporate Governance in increasing corporate tax compliance - Abdul Rasyid (Jurnal Info Sains : Informatika dan Sains, 2023)
The primary objective of this study is to examine the impact of Good Corporate Governance (GCG) on enhancing corporate taxpayer compliance. The acronym GCG stands for good corporate governance, which encompasses a range of managerial strategies aimed at promoting transparency, accountability, and ethical conduct within an organization's activities. The present study employs a qualitative methodology utilising descriptive techniques. The findings of the study indicate that the implementation of Good Corporate Governance (GCG) principles within the realm of taxation has a favourable influence on the extent to which companies adhere to their tax responsibilities. The principles of Good Corporate Governance (GCG), including Transparency, Accountability, Responsibility, Independence, and Fairness, contribute to the establishment of an organisational setting in which corporations conduct their activities with a commitment to integrity. By adhering to these values, companies are able to steer clear of engaging in contentious tax practises and ensure their compliance with tax rules. Furthermore, the incorporation of good corporate governance (GCG) practises in the realm of taxes not only serves to mitigate legal and reputational concerns, but also fosters the establishment of trust among shareholders, stakeholders, and society at large. Moreover, it serves as a robust basis for the sustainable growth of the firm. Therefore, the implementation of good corporate governance (GCG) in the realm of taxation offers two-fold advantages: enhancing companies' adherence to tax regulations and facilitating ethical and socially responsible business practises.